INFLUENCE OF VARIOUS FACTORS ON THE FREQUENCY OF COMPLICATIONS IN SKELETAL POLYTRAUMA AFTER INTERHOSPITAL TRANSPORT AND AT THE INTENSIVE CARE UNIT (World Science, 2021)
The study involved 240 patients with skeletal polytrauma. The aim of the study was to improve the results of treatment of victims with skeletal polytrauma by substantiating methods for predicting and preventing various complications after interhospital transportation and in the intensive care unit. We found that after interhospital transportation of patients, the following complications were detected: fatty embolism (11.6%), anemic syndrome (51.7%), acute respiratory failure (20.3%), pneumonia (13.4%). The main defects at the hospital stage were: incomplete laboratory and instrumental studies (81.7%), untimely surgical osteosynthesis (49.2%), undiagnosed complications (31.2%), underestimation of the severity of the condition (30%), inadequate correction of hypovolemia, anemic syndrome, coagulopathy (51.7%, 81.7%, 63.3%, respectively), inadequate prevention of thromboembolic complications and fatty embolism (70%, 51.7%), inadequate correction of acid-base disorders and dyselectrolytemia (100%).